2015
DOI: 10.1016/j.foodres.2015.07.010
|View full text |Cite
|
Sign up to set email alerts
|

Effect of extruded wheat flour and pre-gelatinized cassava starch on process and quality parameters of French-type bread elaborated from frozen dough

Abstract: This study aimed to verify the potential of extruded wheat flour (EWF) or pre-gelatinized cassava starch (PGS) to improve the process and the quality of French bread elaborated from frozen dough. Three formulations were prepared: 100% control wheat flour (CWF) and the other two formulations with 5% substitution of wheat flour by EWF or PGS. Frozen doughs were frozen stored for seven days and after this period they were thawed, fermented, baked and evaluated for physical, chemical and technological characterist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(24 citation statements)
references
References 24 publications
1
22
0
1
Order By: Relevance
“…It is noted that the apparent viscosity curves for masa incorporating GMF appear as a vertical shift of the curve for M 0 , suggesting that the GMF acted as a hydrocolloid strengthening the masa microstructure. Hydrocolloids added to masa have the ability to disperse and absorb more water as compared with native starch . It has been pointed out that the viscosity of colloidal dispersions incorporating gelatinized starch is ascribable to liquid absorption and resultant swelling of the dispersed colloid .…”
Section: Resultsmentioning
confidence: 99%
“…It is noted that the apparent viscosity curves for masa incorporating GMF appear as a vertical shift of the curve for M 0 , suggesting that the GMF acted as a hydrocolloid strengthening the masa microstructure. Hydrocolloids added to masa have the ability to disperse and absorb more water as compared with native starch . It has been pointed out that the viscosity of colloidal dispersions incorporating gelatinized starch is ascribable to liquid absorption and resultant swelling of the dispersed colloid .…”
Section: Resultsmentioning
confidence: 99%
“…It has been reported that lower screw speeds result in a longer residence time which encourages prolonged shearing, subsequently affecting the starch content (Ziegler and Aguilar 2003). In addition, Ortolan et al (2015) reported that extrusion processing significantly (P<0.05) reduces the protein content in the extruded wheat flour. The observed reduction in protein and starch content in the extruded samples might be related to the cross-linking of protein and starch and the gelatinization of starch (Kim et al 2006).…”
Section: Proximate Analysismentioning
confidence: 99%
“…Viscosity was increased due to the hydroxyl groups in the hydrocolloid structure, which allowed more water interactions through hydrogen bonding (Rosell et al 2001). In this way, hydrocolloids added to dough have the ability of dispersing and absorbing more water as compared to native starch (Ortolan et al 2015). According to Li and Nie (2016), the viscosity of the pregelatinized starch contained in colloidal suspensions was increased by the thickening of the liquid phase attributed to liquid absorption and resultant swelling of the dispersed colloid.…”
Section: Discussionmentioning
confidence: 99%